Physico-chemical and microbiological qualities of raw goat milk and antibacterial characteristics of isolated lactic acid bacteria - Lai, Chia Yee (2014)
Raw goat milk is recognized as a nutritious food owed to its originality and medicinal values. In recent years, people consumed goat milk more frequently for its natural health promoting components. However, data for quality and safety of the locally produced raw goat milk are scarcely available. There is no official quality and safety standard to describe on raw goat milk. Only the total bacterial count is used as the main quality or safety measure. This is not adequate as there are numbers of food-borne related facts. The contamination of the milk proper storage temperature and duration should be accounted for public notifications due to food safety concerned. This study aimed to evaluate the microbiological quality and safety of stored raw goat milk prior to further processing steps. In platform tests, milk samples passed organoleptic test and Clot On Boiling test but were mostly (88.89 %) failed in alcohol test. The proximate composition, the water content of milk samples were relatively high while the remained contents of protein, fat, carbohydrates and ash are much lower than the reference values. In general, results obtained from physico-chemical analysis showed contents of local milk samples were partially in lined with reported literature due to subjective factors of breeds, geographical areas and feeds. There was no significant difference observed in pH values of milk samples in comparison to the reported data. Initial total plate count,coliform count and proteolytic count determined were 3.44 log cfu/ml, 1.87 log cfu/ml and 1.97 log cfu/ml respectively. Storage time showed significant effect on the bacterial counts (p<0.05) of milk samples. Milk samples were kept and observed up to 12 hours under ambient temperature (3.95 log cfu/ml) had not exceeded guidelines limit of total aerobic count for food. The shelf-life of the milk samples were extended up to 10 days storage under refrigerated temperature of 4°C. A total of 150 Lactic Acid Bacteria (LAB) isolates were determined to a presumptive genus level and numbers were selected for species identification using the BIOLOG System. Among the isolated LAB species from goat milk samples, identified were Lactobacillus buchneri, Lactobacillus brevis, Enterococcus casseliflavus, Enterococcus faecium and Weissella viridescen. Bacteriocin Like Inhibitory Substance (BLIS) were obtained from the identified LAB species and further verified on their antibacterial activity. There was at least one level of variables have significantly affect the antibacterial activity towards selected Gram-positive test bacteria, ATCC 19155 Listeria monocytogenes, Staphylococcus aureus and Streptococcus spp. Besides, BLIS goat milk LAB species had shown significant effect (p-value<0.05) on antibacterial activity against selected Gram-negative test bacteria such as Escherichia coli (E. coli), Pseudomonas spp.,Klebsiella spp., ATCC 14028 Salmonella typhimurium and Serratia marcescens. BLIS produced by Lactobacillus brevis and Lactobacillus buchneri isolated from the goat milk spoilage bacteria has shown potent inhibition against Listeria monocytogenes,Staphylococcus aureus, Escherichia coli and Salmonella typhimurium. These findings emphasized the importance of microbiological quality study of locally produced raw goat milk and screening of more novel LAB species with their antibacterial activities.